Neuro-Oncology Practice Clinical Debate: stereotactic radiosurgery or fractionated stereotactic radiotherapy following surgical resection for brain metastasis. Issue 3 (1st October 2019) - Palmer, Joshua D; Greenspoon, Jeffrey; Brown, Paul D; Johnson, Derek R; Roberge, David
Abstract: The treatment of resected brain metastasis has shifted away from the historical use of whole-brain radiotherapy (WBRT) toward adjuvant radiosurgery (stereotactic radiosurgery [SRS]) based on a recent prospective clinical trial demonstrating less cognitive decline with the use of SRS alone and equivalent survival as compared with WBRT. Whereas all level 1 evidence to date concerns single-fraction SRS for postoperative brain metastasis, there is emerging evidence that fractionated stereotactic radiotherapy (FSRT) may improve local control at the resected tumor bed. The lack of direct comparative data for SRS vs FSRT results in a diversity in clinical practice. In this article, Greenspoon and Roberge defend the use of SRS as the standard of care for resected brain metastasis, whereas Palmer and Brown argue for FSRT.